Profiles of volatile sulfur compounds in various vegetables consumed in Korea using HS-SPME-GC/MS technique - Park, Samuel; Kim, Heon-Woong; Joo Lee, Chang; Kim, Younghwa; Sung, Jeehye (Frontiers in Nutrition, 2024)
Volatile sulfur compounds (VSCs) are not only important for their therapeutic potential but also significantly influence the flavor profiles of agricultural products. VSCs exhibit various chemical structures due to their stability and volatility, and they may form or be altered as a result of enzymatic and chemical reactions during storage and cooking. This study has focused on profiles of VSCs in 58 different vegetable samples by using HS-SPME-GC/MS technique and chemometric analyses. The validation was carried out using cabbage juice as a vegetable matrix for VSCs analysis, showing satisfactory repeatability (RSD 8.07% ~ 9.45%), reproducibility (RSD 4.22% ~ 7.71%), accuracy and specificity. The established method was utilized on various vegetables, revealing that 21 VSCs such as sulfides, disulfides, trisulfides, isothiocyanates, sulfhydryls, and thiophenes were successfully identified and quantified. These compounds were found in a range of vegetables including Allium species, Cruciferae, Capsicum species, green leafy vegetables, and mushrooms. In particular, isocyanate and allyl groups were abundant in Cruciferae and Allium vegetables, respectively. Cooking conditions were shown to reduce the levels of certain sulfur compounds such as dimethyl sulfide and dimethyl trisulfide in vegetables like broccoli and cabbage, suggesting that heat treatment can lead to the volatilization and reduction of these compounds. The present study provides reliable insights into the compositions of VSCs in various vegetables and examines the changes induced by different cooking methods.